Investigating the level of compliance among domestic tourists towards new travel standard operating procedures (SOPs) during Covid-19 pandemic in Malaysia - Nurul Azira Muhamad Aznor; Rose Khaleeda Rosman; Zahidah Mad Loddin; Nooriffah Diyanah Matbali (2021)
The COVID-19 pandemic has impacted the tourism industry in Malaysia due to travel restrictions imposed by the government. However, to minimize the impact on the country’s economy, the government is allowing the travel sector remained open by implementing several standard operating procedures (SOPs) to curb the pandemic. The main objective of this research is to investigate the level of compliant among domestic tourists towards the new travel SOPs during COVID-19 pandemic. A convenient sample of 400 tourists both from Peninsular Malaysia and East Malaysia were surveyed and analyzed. The result indicates that majority of domestic tourists were aware of the new travel SOPs, and they did their level best to comply with. This study concludes that domestic tourists in Malaysia say that domestic tourists can travel as usual and only need to go through a new normal life with the recovery phase of the COVID-19 case and must comply to standard operating procedures (SOPs) set by the government to prevent the epidemic from spreading further.